CONDITIONS OF HISTORICITY OF HUMAN EXISTENCE AND HISTORY HUMANITY ACCORDING TO JASPERS - V. V. Khmil; O. M. Korkh (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The research is aimed at understanding Jaspers' ideas concerning independent self-determination of a special and distinctive identity as a main condition of history humanity and historicity of human existence. The research is based on ideological heritage of Karl Jaspers, as well as cultural and historical analysis on the basis of historical, logical and comparative principles reflected in the papers of national and foreign scientists. As a result, it made possible to model cultural and historical context, philosophical and theoretical origins and world view intentions of the German philosopher. Originality. The analysis has shown that the key concepts of Jaspers' philosophy were focused to determine and substantiate a main condition of historical dynamics and humanism, namely the existence of a unique and distinctive identity able to create and generate new values that can turn into universal ones and give impetus to our society and promote its further humanization. Conclusions. According to this investigation, Jaspers' key concepts are immanently subject to justifying the conditions of history humanity and historicity of human existence. In their unity they allow us to adequately understand connection between social dynamics and humanism with unique individuals and distinctive identities that can create and generate new values with further social development prospects. Favourable conditions for these unique individuals to appear prevent from numerous unsafe challenges, which are a certain threat to our society. And on the contrary, if there are no such conditions for a human, he is prone to any totalitarianism, personal crime and can be a faithful servant of any leader.